Ablative fractional laser-assisted low-irradiance photodynamic therapy for treatment of actinic keratoses in organ transplant recipients: a prospective, randomized, intraindividual controlled trial - Lonsdorf, Anke Susanne; Keller, Aric; Hartmann, Julia; Enk, Alexander; Gholam, Patrick (Acta dermato-venereologica, 2022)
Pain and inferior efficacy are major limiting factors of conventional photodynamic therapy for the field treatment of actinic keratoses in immunosuppressed organ transplant recipients. This prospective randomized controlled study evaluates the efficacy and tolerability of ablative fractional laser system pretreatment combined with low-irradiance photodynamic therapy (18.5 mW/cm2) compared with conventional photodynamic therapy (61.67 mW/cm2) in the treatment of actinic keratoses on the face and scalp in organ transplant recipients, using a red light-emitting diode lamp at a total light dose of 37 J/cm2. Low-irradiance photodynamic therapy combined with Er:YAG pretreatment achieved a significantly superior lesion response rate (mean ± standard deviation 77.3 ± 23.6%) compared with conventional photodynamic therapy (61.8 ± 21.4%; p = 0.025) in intra-individual fields at 3 months without negatively impacting pain (p = 0.777) or cosmetic outcome (p = 0.157).